Validation of Fistula Risk Score calculator in diverse North American HPB practices. Issue 6 (June 2017) - Grendar, Jan; Jutric, Zeljka; Leal, Julie N.; Ball, Chad G.; Bertens, Kimberly; Dixon, Elijah; Hammill, Chet W.; Kastenberg, Zachary; Newell, Pippa H.; Rocha, Flavio; Visser, Brendan; Wolf, Ronald F.; et al.
Abstract: Background: Fistula Risk Score (FRS) is a previously developed tool to assess the risk of clinically relevant postoperative pancreatic fistula (CR-POPF) following pancreatoduodenectomy (PD). Methods: Prospectively collected databases from 4 university affiliated and non-affiliated HPB centers in United States and Canada were used. The influence of individual baseline characteristics, FRS and FRS group on CR-POPF was assessed in univariate and multivariate analyses. FRS calculator performance was assessed using a C-statistic. Results: 444 patients were identified. Pathology, soft pancreas texture and pancreatic duct size were associated with CR-POPF rates (p < 0.001 for each); EBL was not (p = 0.067). The negligible risk group consisted of 50 (11.3%) patients, low risk of 118 (26.6%), moderate 234 (52.7%) and high risk group of 42 (9.5%) patients. The overall rate of CR-POPF was 20%. Of the patients in the negligible risk group, 2% developed CR-POPF, 13.6% of the low risk, 23.1% moderate and 42.9% in the high risk group (p < 0.001). Overall C-statistic was 0.719. Conclusion: FRS is robust and able to stratify the risk of developing CR-POPF following PD in diverse North American academic and non-academic institutions. The FRS should be used in research and to guide clinical management of patients post PD in these institutions.